Developing A Moodle-Based Learning Management System (LMS) for Slow Learners - J. Priyanto Widodo; Lailatul Musyarofah; Joko Slamet (Jurnal Inspirasi Pendidikan, 2022)
This study aimed to develop a Moodle-based Learning Management System (LMS) called eLSIDA (e-Learning STKIP PGRI Sidoarjo Asistif), which is validly used by students slow to study at STKIP PGRI Sidoarjo. This study used 3 out of 5 ADDIE models, namely Analysis, Design, and Development. Expert judgment in this study consists of two experts, material experts, and media experts. The research instrument used to obtain research data is a questionnaire. The data that has been obtained is then analyzed using descriptive analysis. Validation results from material experts obtained a score of 92.5%, while the results of media expert validation obtained a score of 95%. Based on the expert judgment assessment shown that eLSIDA that has been developed in general can be declared valid and worth to be used. The media that has been developed can be accessed through http://lms.elsida.ac.id/Although the development of eLSIDA has been considered valid, the effectiveness of the media on eLSIDA needs to be tested further.